The Importance of Student’s Representation in the Governance Structure of Historically Black Universities in South Africa - Felix Omal (Journal of Interdisciplinary Sciences)
This paper was developed from a study that looked at the role of the university council in bringing about effective governance in a South African historically black university. Institutional governance is concerned with notion of power and how it is managed to bring about desired objectives. As such perceptions are fundamental to this process. In the post-1994 transformation of the South African higher education system, university governing bodies were put in charge of the transformation of the universities under their leadership. Through the State policy of cooperative governance, the State demanded that university councils create governance structures and systems where different institutional stakeholders are to participate in the university governance process to achieve the goals of university transformation. However, the processes of implementation were challenged by stakeholder contestations around issues of contextual interpretation. Since 1994 several stakeholder groups have always been on strikes and protests over unfulfilled expectations and unresolved historical imbalances. This paper examines how student issues are being handled through university students’ vivid representation in the internal governance structures and, also, how such representation could bring about effective governance across historically black universities in South Africa. This paper argues that proper handling of university student issues is significant for the university transformation, especially as regards historically black universities in South Africa. The paper ends with a re-imagination of stakeholders’ representation in the different internal governance structures of historically black universities in South Africa for further research.